Response of Erythrocyte Membranes to Total Body Exposure by 1800 MHz Frequency Microwave Radiation - M. Malakyan; S. Bajinyan; D. Yeghiazaryan; L. Abrahamyan; H. Minasyan
Red blood cells were used to detect possible membrane perturbations as effects of rats total body exposure to 1800 MHz radiofrequency electromagnetic radiation (RFEMR) using 2 different schemes of irradiation: 2-hour single and fractional exposure during 4 consecutive days for 0.5 hour daily. The following characteristic indices of erythrocyte membrane functional indices were analyzed: total permeability for K+ ions, activity of specific Ca2+-activated K+-channels, as well as membrane potential and lipid peroxidation intensity. Our research revealed a biological response of erythrocyte membrane to 1800 MHz frequency RF-EMR at both schemes of irradiation manifested as alterations in functional properties after animal whole body exposure. Moreover, longlasting character of these effects was revealed.
Keywords: Physics; Cross-Disciplinary